Secularism and pluralistic democracy in India - Ragupathy, Varadarajan; Mohan, Vasundhara (Concept Publ. Company, 2013)
Papers presented at a national workshop on "60 years of secularism and pluralistic democracy in India", jointly organized by Centre for Study of Society and Secularism and Department of Political Science and Development Administration of Gandhigram Rural Institute, held at Chennai in April, 2010